The 3‐D distribution of random velocity inhomogeneities in southwestern Japan and the western part of the Nankai subduction zone. Issue 5 (17th May 2013) - Takahashi, Tsutomu; Obana, Koichiro; Yamamoto, Yojiro; Nakanishi, Ayako; Kodaira, Shuichi; Kaneda, Yoshiyuki
Abstract: [1] Seismic waves at high frequencies (>1 Hz) show collapsed and broadened wave trains caused by multiple scattering in the lithosphere. This study analyzed the envelopes of direct S waves in southwestern Japan and on the western side of the Nankai trough and estimated the spatial distribution of random inhomogeneities by assuming a von Kármán type power spectral density function (PSDF). Strongly inhomogeneous media have been mostly imaged at shallow depth (0–20 km depth) in the onshore area of southwestern Japan, and their PSDF is represented as P ( m ) ≈ 0.05 m −3.7  km 3, with m being the spatial wave number, whereas most of the other area shows weak inhomogeneities of which PSDF is P ( m ) ≈ 0.005 m −4.5  km 3 . At Hyuga‐nada in Nankai trough, there is an anomaly of inhomogeneity of which PSDF is estimated as P ( m ) ≈ 0.01 m −4.5  km 3 . This PSDF has the similar spectral gradient with the weakly inhomogeneous media, but has larger power spectral density than other offshore areas. This anomalous region is broadly located in the subducted Kyushu Palau ridge, which was identified by using velocity structures and bathymetry, and it shows no clear correlation with the fault zones of large earthquakes in past decades. These spatial correlations suggest that possible origins of inhomogeneities at Hyuga‐nada are ancient volcanic activity in the oceanic plate or deformed structures due to the subduction of the Kyushu Palau ridge. Key Points: Random inhomogeneities in SW Japan are estimated by the peak delay time analysis Presence of volcanic rocks is a possible origin of strong inhomogeneities Subducted Kyushu Palau ridge shows anomalous random inhomogeneity